2019
DOI: 10.7554/elife.46497
|View full text |Cite
|
Sign up to set email alerts
|

Single-amino acid variants reveal evolutionary processes that shape the biogeography of a global SAR11 subclade

Abstract: Members of the SAR11 order Pelagibacterales dominate the surface oceans. Their extensive diversity challenges emerging operational boundaries defined for microbial 'species' and complicates efforts of population genetics to study their evolution. Here, we employed single-amino acid variants (SAAVs) to investigate ecological and evolutionary forces that maintain the genomic heterogeneity within ubiquitous SAR11 populations we accessed through metagenomic read recruitment using a single isolate genome. Integrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
147
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(178 citation statements)
references
References 89 publications
(121 reference statements)
14
147
1
Order By: Relevance
“…However, a genome reconstructed from a clonal microbial culture also does not represent the cloud of biologically important variation that exists in the natural population from where the isolate was derived. Population diversity can be analyzed by comparing all individual sequences (or short reads) to the metagenome-assembled reference genome (Simmons et al 2008;Delmont et al 2019) . While some populations are near-clonal, others are very complex strain mixtures and yet others fall on the continuum between these (Lo et al 2007;Chivian et al 2008;Simmons et al 2008) .…”
Section: Introductionmentioning
confidence: 99%
“…However, a genome reconstructed from a clonal microbial culture also does not represent the cloud of biologically important variation that exists in the natural population from where the isolate was derived. Population diversity can be analyzed by comparing all individual sequences (or short reads) to the metagenome-assembled reference genome (Simmons et al 2008;Delmont et al 2019) . While some populations are near-clonal, others are very complex strain mixtures and yet others fall on the continuum between these (Lo et al 2007;Chivian et al 2008;Simmons et al 2008) .…”
Section: Introductionmentioning
confidence: 99%
“…However, a genome reconstructed from a clonal microbial culture also does not represent the cloud of biologically important variation that exists in the natural population from where the isolate was derived. Population diversity can be analyzed by comparing all individual sequences (or short reads) to the metagenome-assembled reference genome (Simmons et al 2008;Delmont et al 2019). Although some populations are near-clonal, others are very complex strain mixtures, and yet others fall on the continuum between these (Lo et al 2007; Chivian et al 2008;Simmons et al 2008).…”
mentioning
confidence: 99%
“…Schloissnig et al 23 conducted pioneering cross-continental comparative analyses of human gut microbiomes using this approach and showed that there is more intraspecific genetic differentiation between habitats (human individuals) than within the same habitat over time. Similar approaches have been used by Nayfach et al 10 and Delmont et al 24 to show that gene content and amino acid composition, respectively, differ between oceanic regions within individual bacterial species.…”
Section: Introductionmentioning
confidence: 81%
“…Our results suggest that bacterioplankton do not only modulate the flexible gene pool when confronted by environmental clines, as demonstrated by several studies 10,52,53 , but also adapt by modifying existing genes (altering allele frequencies) to the different environmental conditions. Delmont 24 suggested an evolutionary mechanism for such conservation of genetic heterogeneity by emphasizing the role of consistent purifying selection against deleterious non-synonymous variants, exemplified by the cosmopolitan SAR11 clade. The same authors showed a partitioning of SAR11 metagenomes in concordance with large-scale oceanic temperatures suggesting that environmental selection is of central importance even at the microdiversity level in marine bacterioplankton.…”
Section: Discussionmentioning
confidence: 99%